Digital image processing methods - Dougherty, Edward R. (Optical engineering (Marcel Dekker, Inc.), 1994)
This unique reference presents in-depth coverage of the latest methods and applications of digital image processing describing various computer architectures ideal for satisfying specific image processing demands.